Determinasi Kinerja Pemerintah Desa di Kecamatan Widang Kabupaten Tuban - Devia Ratna Sari; Fajar Syaiful Akbar (Journal of Management and Bussines (JOMB), 2023)
This research aims to show and evaluate the impact of openness and community involvement on the effectiveness of village government in Widang-Tuban District. Purposive sampling is the method used in this research, and was carried out using a set of criteria. The testing model (outer model) and structural model (inner model) are two of the model sub-chapters that form the analysis method (SEM). Outside the model, convergent validity, discriminative validity, and reliability are three tests. The R, Q, and FIT model tests form the inner model, conversely. Research result. The conclusion is that transparency has a positive effect on the performance of the village government and secondly community participation has a positive effect on the performance of the village government. Keywords: Community Participation, Transparency, Government Performance